2014
DOI: 10.3344/kjp.2014.27.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine-induced Vasodilation Is Mediated by Decreased Calcium Sensitization in Isolated Endothelium-denuded Rat Aortas Precontracted with Phenylephrine

Abstract: BackgroundA toxic dose of bupivacaine produces vasodilation in isolated aortas. The goal of this in vitro study was to investigate the cellular mechanism associated with bupivacaine-induced vasodilation in isolated endotheliumdenuded rat aortas precontracted with phenylephrine.MethodsIsolated endothelium-denuded rat aortas were suspended for isometric tension recordings. The effects of nifedipine, verapamil, iberiotoxin, 4-aminopyridine, barium chloride, and glibenclamide on bupivacaine concentration-response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…However, in the current study, a toxic dose of bupivacaine inhibited sodium orthovanadate-induced MYPT1 phosphorylation. It has been reported that bupivacaine inhibits calcium sensitization in aortae precontracted with PDBu, NaF and phenylephrine [12,13,14]. In agreement with previous reports and the present Western blot results, bupivacaine decreased more tension than [Ca 2+ ] i during sodium orthovanadate-induced contraction, suggesting that the bupivacaine-induced reduction in calcium sensitization is mediated by the inhibition of sodium orthovanadate-induced MYPT1 phosphorylation [12,13,14].…”
Section: Discussionsupporting
confidence: 92%
“…However, in the current study, a toxic dose of bupivacaine inhibited sodium orthovanadate-induced MYPT1 phosphorylation. It has been reported that bupivacaine inhibits calcium sensitization in aortae precontracted with PDBu, NaF and phenylephrine [12,13,14]. In agreement with previous reports and the present Western blot results, bupivacaine decreased more tension than [Ca 2+ ] i during sodium orthovanadate-induced contraction, suggesting that the bupivacaine-induced reduction in calcium sensitization is mediated by the inhibition of sodium orthovanadate-induced MYPT1 phosphorylation [12,13,14].…”
Section: Discussionsupporting
confidence: 92%
“…However, orders of magnitude below their sodium channel blocking threshold, 36 , 37 they can interfere with intracellular signaling, 38 and above their sodium channel blocking threshold, they interfere with mitochondrial metabolism, thereby altering oxidative phosphorylation 39 . These multiple effects lead to a combination of systematic issues with both vasodilation 40 and cardiac collapse 41 . It is still unclear which effect is responsible for the lethality of LAST 9 .…”
Section: Part I: Introduction and Overviewmentioning
confidence: 99%
“…Low doses of levobupivacaine produce vasoconstriction at the resting tension, whereas high doses of levobupivacaine cause vasodilation, which appears to be associated with vascular collapse evoked by such high doses of levobupivacaine 6 - 8 . In addition, a toxic dose of bupivacaine induces vasodilation that appears to be partially associated with decreased calcium sensitization in isolated endothelium-denuded rat aorta precontracted with phenylephrine 9 . Agonists, including phenylephrine, activate Rho kinase and protein kinase C (PKC), which leads to contraction via increased calcium sensitization 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Rho kinase and PKC phosphorylate myosin phosphatase target subunit 1 (MYPT1) and phosphorylation-dependent inhibitory protein of myosin phosphatase, respectively, leading to increased calcium sensitization via the inhibition of myosin light chain phosphatase (MLCP) 10 . Because the phosphorylation of MYPT1, which is a signaling molecule downstream of Rho kinase that participates in vascular smooth muscle contraction, is involved in calcium sensitization, whereas bupivacaine-induced vasodilation causes decreased calcium sensitization, we tested the hypothesis that lipid emulsion attenuated bupivacaine-induced vasodilation via the modulation of MYPT1 phosphorylation 3 - 5 , 9 , 10 . The goal of this in vitro study was to investigate the cellular mechanism responsible for the lipid emulsion-mediated attenuation of severe vasodilation induced by a toxic dose of bupivacaine, focusing on MYPT1 phosphorylation.…”
Section: Introductionmentioning
confidence: 99%